The Power Rainbow: a tool to support 3rd–5th graders in analyzing systems of power - Mariën, Hania K.; Kirby, Anna L. (Frontiers in Education, 2023)
Drawing on scholars of critical theory and pedagogy, we understand power as operating within nested social systems, meaning that individuals experiencing injustice are impacted not only by the most immediate agent of that injustice but also by the broader institutions, policies, and values of their society. The practice of attending to power and how it shapes our societies at multiple levels (i.e., power analysis) is necessary to critical research approaches, including Critical Participatory Action Research (CPAR). While adolescents and adults (the age groups most commonly engaging in CPAR) are likely to have developed some understanding of systems of power through experience, dialog, and/or educational experiences, children participating in CPAR have generally had fewer opportunities to develop this type of analysis. In our own CPAR projects with 3rd–5th grade children, we have witnessed the challenges and possibilities of exploring power with child CPAR team members. In this paper, we introduce a methodological tool that we developed to facilitate power analysis during critical research projects like these: The Power Rainbow. The Power Rainbow is a graphic representation of nested systems of power, which can be utilized with children in multiple ways throughout the CPAR process. The tool concretizes the abstract concept of systemic power through shape, color, and text, and scaffolds the type of structural thinking necessary to research and take action towards more just futures.